Generation of defective interfering particles of Semliki Forest virus in a clone of Aedes albopictus (mosquito) cells. - Logan, K B (1979)
Serial undiluted passage of Semliki Forest virus in a clone of Aedes albopictus cells resulted in a marked decrease in infectious virus yields due to the generation and accumulation of defective interfering particles. Virus from the third passage had a high particle/infectivity ratio and interfered specifically with homologous but not heterologous standard virus replication. Two RNA species of molecular weights 0.78 X 10(6) and 0.61 X 10(6) were the major RNA components of purified passage 4 virus. These RNA species were also the predominant virus RNA species detected in cells infected with passage 3 virus. Synthesis of standard virus RNA and virus-specified protein was much reduced in passage 3 virus-infected cells. Interference with standard virus replication and the synthesis of large amounts of defective interfering RNA were also observed in chicken embryo cells infected with passage 3 virus from mosquito cells.